The Contribution of Parents and Teachers to Bullying Attitudes in Islamic Boarding Schools - Mega Adyna Movitaria; Rahmatul Fadilah; Wisda Rahmadinur (International Journal of Research, 2023)
The purpose of this study was to find out how Bullying behavior occurs in Islamic boarding school students Nurul Yaqin Ringan-ringan, what factors cause Bullying behavior, as well as the role of parents and society in the efforts of students to control Bullying behavior in Islamic boarding schools. This study used a qualitative method in which this case went through a process of observation, in-depth interviews and document analysis. The results of the study involving several informants, such as teachers, students and parents, showed that there were two forms of Bullying behavior, mild and severe. Factors that cause Bullying behavior are internal and external factors. Efforts made by parents and teachers to control Bullying behavior are preventive and repressive measures. Preventive actions, such as reprimanding and supervising students as well as imposing sanctions or punishments that identify Bullying behavior, as well as cooperation between the pesantren and parents to minimize the occurrence of Bullying behavior